EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DAN MOOD UNDERSTAND RECALL DETECT ELABORATE REVIEW (MURDER) PADA MATERI POKOK LOGARITMA DITINJAU DARI MINAT BELAJAR SISWA KELAS X SMK SE KABUPATEN KARANGANYAR - Mustaqim, Burhan; Riyadi, Riyadi; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research aims at knowing (1) the effectiveness of TPS, MURDER and Direct Instruction model to the students achievement on mathematics, (2) which learning model TPS, MURDER and Direct Instruction, having better achievement on mathematics viewed from studentsâ interest, (3) studentsâ achievement viewed from studentsâ interest on each learning model. This research is experimental research using factorial design 3x3. The population is students of SMK on technique program in Karanganyar. Sampling is stratified cluster random sampling. The sample is 300 students, 100 is first experimental class, 100 is second experimental class and 100 is control class. Collecting data has been done through multiple choice test to know studentsâ achievement and questionnaire to know students interest in learning. Instrument test and questionnaire were tested before it is used to take data. Instrument validities test and questionnaire were carried out by validator, reliability test was tested by formula KR-20 and reliability questionnaire was tested with formula Cronbach Alpha while its data analysis technique uses two-way analysis of variance with unequal cells. From the result was concluded that: (1) Students who are taught using cooperative learning model, MURDER, have better achievement than TPS and Direct Instruction. Those taught by using TPS have better achievement than Direct Instruction. (2) Viewed from studentsâ interest, high, mid, and low, taught by using learning MURDER have better achievement than TPS and those taught by using TPS have better achievement than Direct Instruction. (3) Viewed from learning model MURDER, TPS, and Direct Instruction, students having high interest have better achievement than those students having mid interest and students having mid interest have better achievement than those students having low interest.Keywords: MURDER, TPS, Interests Learning, Students Achievement on mathematics.